Comparison of classical and affinity purification techniques of Mason-Pfizer monkey virus capsid protein: the alteration of the product by an affinity tag - Rumlová, M; Benedíková, J; Cubínková, R; Pichová, I; Ruml, T (Protein expression and purification, 2001)
The efficiencies of different procedures for purification of the capsid protein (CA) of Mason-Pfizer monkey virus are compared. Plasmids encoding both wild-type CA and two C-terminally modified sequences of CA suitable for affinity chromatography purification were prepared. CA was expressed in Escherichia coli (i) as a wild-type protein, (ii) C-terminally extended with a six-histidine tag (CA 6His), and (iii) as a protein containing a C-terminal fusion to a viral protease cleavage site followed by a six-histidine tag (CA 6aa6His). Electron microscopy was used for comparison of the resulting proteins, as CA is a structural protein with no enzymatic activity. We have found that these C-terminal fusions dramatically influenced the properties and morphology of structures formed by CA protein in E. coli. The formation of amorphous aggregates of CA was abolished and CA 6His and CA 6aa6His proteins formed organized structures. CA and CA 6aa6His accumulated in bacteria in inclusion bodies as insoluble proteins, CA 6His was found in a soluble form. Both six-histidine-tagged proteins were purified using affinity chromatography under either native (CA 6His) or denaturing (CA 6aa6His) conditions. CA protein was purified under denaturing conditions using gel-filtration chromatography followed by refolding. All proteins were obtained at a purity >98%. Both aforementioned C-terminal extensions led to dramatic changes in behavior of the products and they also affected the tendency to form organized structures within E. coli. We show here that the widely used histidine anchor may significantly alter the properties of the protein of interest.
Keywords: Inclusion Bodies; Recombinant Fusion Proteins; buněčná inkluze; Endopeptidases; vazebná místa; Cloning, Molecular; klonování DNA; rekombinantní fúzní proteiny; rozpustnost; elektronová mikroskopie; chromatografie afinitní; Binding Sites; kapsida; Microscopy, Electron; Capsid; endopeptidasy; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; Chromatography, Affinity; Histidine; Solubility; histidin